Karakteristik Perusahaan dan Corporate Governance terhadap Tax Avoidance - Nathania Karta Djaya; Arya Pradipta (Media Bisnis, 2022)
The purpose of this study is to find out empirical evidence of components that affect the tax avoidance. The components that affect it are Return on Assets (ROA), company size, capital intensity, independent commissioner, age firm, leverage, audit committee, and inventory intensity. This study chooses manufacturing companies as the samples. The data were obtained from manufacturing company’s financial statement that listed in Indonesia Stock Exchange (IDX) from the years 2018 until 2020. After selecting the sample using purposive sampling technique, the of 61 companies was obtained with a total of 183 data. To analyze the correlation of independent variable to dependent variable, which is tax avoidance, this study using multiple regression technique. The conclusion of this study is audit committee affect tax avoidance. Many members of the audit committee provide coverage to be able to intervene in determining tax policies in the company. The more the number of audit committees (AC), the higher the level of tax avoidance activities. While Return on Asset (ROA), company size, capital intensity, independent commissioner, age firm, leverage, and inventory intensity do not affect tax avoidance.